Peter Riismøller - Ingen, Ingen (Kuml, 1969)
Peter Riismøller 65 years Immediately after leaving University in 1936, where he had studied history and Danish, Peter Riismøller was appointed to a newly established post at the Aalborg Historical Museum, where he has worked ever since, from 1960 as director. He was born on 14th March 1905 in Skørping in Himmerland, and it was in Himmerland and Aalborg that he subsequently operated. He was thus well equipped to tackle the many problems facing a museum which covers the period from the first settlement of hunters in the district, to modern times, and interval of ten thousand years. As a student, Riismøller worked for a couple of years at the National Museum, among other things on the exhibition of the prehistoric collection in the new museum, but also in the field, at the excavation of the Ladby ship. He had by then gained his first experiences of excavation at the Stone Age village of Troldebjerg, under Johannes Brøndsted, who was both keeper of the prehistoric collections at the National Museum and his teacher at the University. For Brøndsted, Riismøller wrote special papers on the Iron Age gold bracteates, and his extensive knowledge of, for example, mythology and place names were of great value to him and his fellow students. Brøndsted played an important role in the establishment of the new museum post at Aalborg, and Riismøller considered himself Brøndsted’s loyal follower in northern Jutland. Riismøller’s achievement there were numerous, comprising all periods. He was, in particular, a pioneer among urban archaeologists, playing a large part in the investigations into early Aalborg, on which he has written excellent papers -his annual New Year’s greeting to friends and colleagues all over Scandinavia. His always exceptionally well-written papers, many of which are already rarities of our topographical literature, extend from “Fra Svendekro til Lavshus”, 1940 to “Sultegrænsen”, 1968. His opus “Danske Glas, 1825-1925”, has more than doubled the price of our antique glass. Following up this fundamental study, Riismøller has successfully excavated ancient glass works in Jutland. Peter Riismøller started his pioneer work at Aalborg Historical Museum alone, enormously increasing the collection and quickly collecting a group of able collaborators. The Museum is soon to be handed over to a successor, but then he will be able to devote all his time to publication of the extensive cultural material he has collected during a lifetime.